2019
DOI: 10.1016/j.jinf.2018.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterium tuberculosis prosthetic joint infections: A case series and literature review

Abstract: M. tuberculosis PJI can be controlled with prolonged antituberculosis treatment in most cases, with or without surgical treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…A retrospective medical record review of prosthetic joints infected with M. tuberculosis found that an extended course of antibiotics (18 months) was effective and did not require removal of the joint. 15 We believe that the best option for our patient is an extended course of antituberculous therapy (18 months), which we hope will eliminate the M. bovis infection and forego the need for major open aortic surgery (graft explant and revascularization).…”
Section: Discussionmentioning
confidence: 96%
“…A retrospective medical record review of prosthetic joints infected with M. tuberculosis found that an extended course of antibiotics (18 months) was effective and did not require removal of the joint. 15 We believe that the best option for our patient is an extended course of antituberculous therapy (18 months), which we hope will eliminate the M. bovis infection and forego the need for major open aortic surgery (graft explant and revascularization).…”
Section: Discussionmentioning
confidence: 96%
“…PJI is essentially a surgical disease and the majority of the cases require some form of surgical intervention. The DAIR remains a key element in the management of PJI, especially when the usual pathogens are involved, such as Enterococcus, Staphylococcus, and Streptococcus [13]. For acute PJIs caused by gram-negative bacteria and managed with the DAIR procedure, the prognosis is relatively good.…”
Section: Discussionmentioning
confidence: 99%
“…The initial database queries produced 191 reports; 162 articles were excluded, including those that were duplicates (43), reviews or meta‐analyses (24), descriptions of general periprosthetic joint infections (25), descriptions of hip replacements (14), descriptions of non‐tuberculous mycobacterium infections (all case reports, 14), articles on knee joint tuberculosis replacements (23), and non‐English reports (19) 13–41 . We identified 44 cases of TBPJI described in the 29 selected articles.…”
Section: Methodsmentioning
confidence: 99%